POLEMIK KEBIJAKAN PERMENDIKBUD RISTEK NOMOR 30 TAHUN 2021 TENTANG PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL DI LINGKUNGAN PERGURUAN TINGGI DALAM PERSPEKTIF KEBIJAKAN PUBLIK - Agus Widiarto; Suesilowaty (LPPM STIA Banten, 2022)
On August 31, 2021 Regulation of the Minister of Education, Culture, Research and Technology (Permendikbudristek) Number 30 of 2021 concerning Prevention and Handling of Sexual Violence in Higher Education was stipulated by the Minister of Education,Culture, Research and Technology and promulgated on September 3, 2021. The stipulation of this rule is only one day after the Legislation Agency ( Baleg) DPR RI on August 30, 2021 finally agreed to start from the beginning the process of formulating the Preliminary Draft of the Bill on the Elimination of Sexual Violence (RUU PKS) with a slight change in the title, becoming the Bill on Criminal Acts of Sexual Violence (TPKS). Substantially, the initial draft of this bill has similarities with Permendikbudristek Number 30 of 2021, namely regarding the definition, scope, and content of sexual consent which causes controversy in thecommunity. The controversy, which initially focused on the Bill on the Elimination of Sexual Violence, turned to the Permendikbudristek. This article will review Permendikbudristek in substance and its controversy in the midst of society and the implications it causes. Analysis of public Policy, including in the Formulation and Implementation is used as an approach to unravel various aspects, including the position of this Permendikbudristek in the hierarchical aspect of Indonesian legislation.